LINGUISTIC AND SOCIO-PRAGMATIC INNOVATIONS IN UZBEK INTERNET DISCOURSE: GRAPHO-ORTHOGRAPHIC, LEXICAL, AND SYNTACTIC DIMENSIONS - Toshqo‘ziyeva Madinaxon Abduvohidovna (International Journal of Literature and Language Studies, 2026)
Abstract—This paper explores the rapid evolution of Uzbek digital communication under the influence of global internet platforms (Telegram, Instagram, YouTube) and computer-mediated communication (CMC) technologies. Relying on computer-mediated discourse analysis (CMDA) and cognitive-pragmatic frameworks, we examine how graphic-orthographic shifts (emojis, punctuation duplication, spelling intentional errors), lexical developments (neologisms, loanwords, abbreviations), and syntactic alterations (ellipsis, parceling, agrammatism) manifest in Uzbek online writing. The data corpus of 1,500 user posts and comments reveals that these variations are not merely structural deviations or language decay, but functional strategies driven by the principle of linguistic economy and the pragmatic need to express stance, affect, and social identity in a non-verbal digital space. Furthermore, we trace the historical and cognitive roots of graphical communication, emphasizing the role of Unicode standardization and emoji pragmatics. The study concludes that Uzbek internet discourse represents a dynamic, hybrid speech system that bridges the gap between formal writing and spoken interactions.